New synthetic methodologies from biorenewable resources - Simeonov, Svilen (2014)
In this thesis will be presented new synthetic methodologies for the production of 5- (hydroxymethyl) furfural (HMF) and its derivatives as one important biorenewable platform molecules available via dehydration from sugars. The new approaches aim to overcome the major difficulties related with HMF synthesis and isolation on industrial and laboratory scale and to study the synthesis and possible toxic effects in humans of important HMF derivatives which could be produced on industrial scale in the near future as a replacement of existing fossil based chemical building blocks. Scalable protocol for the isolation of HMF via simple precipitation was developed together with chemo-enzymatic, and heterogeneous chromium catalyzed methodologies for its synthesis from glucose. Biorefinery and biorenewable resources are certainly topics of interest from educational point. Batch and flow student laboratory experiments for the dehydration of fructose to HMF have been optimized to meet this purpose. The synthesis, physical properties, toxicity and some unconventional applications of specific a class Ionic Liquids namely Magnetic ionic Liquids (MIL) were also studied in collaboration with other laboratories. The environmental friendly solvents are certainly an important part of developing more “green” and sustainable chemistry methodologies. The stability, basicity and their effect on the organic transformations performed in relatively newly discovered and based mostly on biorenewable resources ionic fluids namely deep eutectic solvents (DES) were studied. It was discovered that one of the most commonly used urea based DES undergo urea decomposition at unexpectedly low temperatures to form ammonia which was assign as responsible for their observed basicity. The readily available from Lupinus genus alkaloid Lupanine was employed as a platform molecule for the synthesis of new sparteine derivatives. Lupanine is a structural analog of sparteine, bearing amide functionality, which was subjected to various transformations resulting in sparteine analogs with potential biological activity and application in asymmetric catalysis.